Baudelaire, les émotions et la Nouvelle Vague cinématographique : correspondances « lombardiennes » - POP-CURȘEU, Ioan (Studia Universitatis Babeș-Bolyai Dramatica, 2024)
Baudelaire, Emotions and the cinematic New Wave: “Lombardian” Correspondences. Integrating various insights from Patrizia Lombardo’s writings, this paper aims to explore how the filmmakers of the French New Wave related to Baudelaire’s work. Indeed, a close look at the films of Truffaut, Godard, Kast, Chabrol, Rohmer, Rivette, Rouch, Varda, Vadim, Schroeder, Mocky, Pollet shows that these filmmakers often referred to Baudelaire in their works, and even sometimes constructed a profoundly Baudelairean aesthetic thinking. There are several elements that explain the Baudelairian passions of the members of the New Wave, in particular the fascination with Parisian inspiration of some authors who no longer work in studios, but also the way in which the poet of The Flowers of Evil treated emotions. The problematization of love in the films of the French New Wave often has Baudelairian overtones, as these filmmakers were marked by the figure of the dandy, but other emotions depicted by them also have a quite obvious poetic ascendancy. In this article, image fragments of films and poems, historical testimonies, as well as writings by these filmmakers who were first film critics are analyzed in a comparative perspective.